Intrinsic fluorescence spectroscopy and detection of pre-invasive lesions of the cervix using portable optical device - Vartika Awasthi; Kiran Pandey; Neelima Singh Chauhan; Asima Pradhan; Bharat L Meena (Barpeta Obstetrics and Gynaecological Society, 2023)
Objectives: To evaluate the screening potential of portable optical device based on the principle of intrinsic fluorescence spectroscopy to detect the fluorescence of FAD molecules in pre-invasive lesions of cervix and its comparison to conventional screening methods. Methods: A prospective cross-sectional study was conducted on 163 patients, who underwent hysterectomy for various gynecological indications. Pap smear and colposcopy was done for all the patients pre-operatively. Cervix from the hysterectomised sample was examined with the optical device, based on the principle of intrinsic fluorescence spectroscopy. The sample was then sent for histopathological examination. The findings of pap smear, colposcopy and fluorescence spectroscopy were correlated with histopathology (gold standard) to find the accuracy of these methods. Results: The sensitivity and specificity for optical device using co-polarized light was 90.5% and 90.9% respectively and for cross polarized light it was 81.1% and 87.3% respectively. The above mentioned results were better for optical device using polarized light as compared to conventional pap smear results. Conclusion: Due to the high sensitivity and specificity, the designed optical device has a potential to be a promising screening tool which can provide see-to-treat protocol and early intervention for pre invasive lesions of cervix.